The transformative impact of GDP, inflation, unemployment, FDI, and trade balance on Southeast Asia’s economy - Febrianto, Anang Catur; Chandrarin, Grahita; Supriadi, Bambang; Rahmawati, Rahmawati; Dwianto, Agus (International Journal of Innovative Research and Scientific Studies, 2025)
This study employs the Threshold Panel Autoregressive (TPAR) model to assess the influence of key macroeconomic factors on economic growth in Southeast Asian nations. The study looks at GDP per capita, inflation, unemployment rate, foreign direct investment (FDI), and trade balance from 2000 to 2023 using secondary data from the World Bank database. The results show that GDP per capita significantly boosts economic growth, and that this effect becomes stronger after it reaches a particular level. Similarly, high unemployment rates show a stronger negative effect, limiting economic expansion, while inflation negatively influences growth, particularly at elevated levels. FDI contributes positively, with a more pronounced effect when investment exceeds a crucial threshold, underscoring its importance in accelerating economic development. The trade balance exhibits a generally positive impact, though its significance fluctuates across different economic conditions. Through threshold analysis, the study identifies transition points at which the relationships between variables shift, offering critical insights for more precise economic policymaking. The results emphasize the necessity of targeted strategies to optimize economic conditions, including policies focused on enhancing GDP per capita, managing inflation and unemployment, attracting foreign investments, and stabilizing the trade balance. By integrating macroeconomic theory with advanced econometric analysis, this study contributes to a deeper understanding of Southeast Asia’s economic dynamics, providing a data-driven foundation for future policy frameworks that foster sustainable economic growth in the region.